2021
DOI: 10.1111/eci.13679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical outcomes of myocarditis and pericarditis in 718,365 COVID‐19 patients

Abstract: Background COVID‐19 has a wide spectrum of cardiovascular sequelae including myocarditis and pericarditis; however, the prevalence and clinical impact are unclear. We investigated the prevalence of new‐onset myocarditis/pericarditis and associated adverse cardiovascular events in patients with COVID‐19. Methods and results A retrospective cohort study was conducted using electronic medical records from a global federated health research network. Patients were included based on a diagnosis of COVID‐19 and new‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 30 publications
3
64
0
2
Order By: Relevance
“…The authors concluded that given the extremely low frequency of myocarditis and the unclear therapeutic implications, the use of endomyocardial biopsy to diagnose myocarditis in the setting of COVID-19 is not recommended. A recent series (22), where 5% of the patients developed new onset myocarditis, confirms these results.…”
Section: Discussionsupporting
confidence: 57%
“…The authors concluded that given the extremely low frequency of myocarditis and the unclear therapeutic implications, the use of endomyocardial biopsy to diagnose myocarditis in the setting of COVID-19 is not recommended. A recent series (22), where 5% of the patients developed new onset myocarditis, confirms these results.…”
Section: Discussionsupporting
confidence: 57%
“…At the time of writing, Australian data on myocarditis in COVID-19 patients were limited (Table 1). Model assumptions on the incidence and CFR of myocarditis in COVID-19 patients were obtained from an international cohort study by Buckley et al [34], and additional unpublished age-sex specific data from the study via personal communication with the lead author. Data showed incidence ranging from 1.66% to 13.74%, and CFR ranging from <1% to 15.14%, depending on age and sex (Supplementary Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…The definitions for vaccine-associated and infection-induced myocarditis used for the model reflect those used within the studies from which data were drawn. Vaccine-associated myocarditis was defined as confirmed myocarditis within approximately 10 days of vaccine administration [31], and COVID-19-related myocarditis was defined as myocarditis that occurred within 6 months of COVID-19 diagnosis [34].…”
Section: Myocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, among 718,365 patients with COVID-19, approximately 6.5% developed new-onset myopericarditis. 5 This higher rate might be an overestimate since most of the patients presented with mild COVID-19 symptoms may not get admitted and diagnosed, thus, not registered with the electronic medical records. Furthermore, our cases represented population-based data locally in Hong Kong, which has practised meticulous contact tracing since the pandemic; the number of total COVID-19 patients in our cohort would, therefore, likely reflect most of the infected patients in the community.…”
Section: Discussionmentioning
confidence: 99%